FILIAL PIETY IN THE QUR’ANIC PERSPECTIVE: A THEMATIC STUDY USING GROUNDED THEORY - Siti Muliya Septiani Turaedi; Muhammad Alif; Raudotul Jannah; Tasya Salsabila; Putri Nabila (Tanzil: Jurnal Studi Al-Quran, 2025)
The concept of filial piety or birr al-wālidayn in the Qur’an is a form of respect, devotion, and a child’s deep sense of loyalty to their parents. This value, when viewed from a moral, social, and spiritual perspective, has a central position in building harmonious family relationships and forming a complete and civilized human character. The phenomenon of increasing disobedience behavior, even disobedience to parents in various contemporary Muslim societies, is a worrying indication and indicates the urgency of revitalizing Islamic ethical values, especially in the context of child-parent relationships. This study uses the method of thematic interpretation (tafsīr mawḍū‘ī) combined with the Constructive Grounded Theory approach to examine in depth 15 relevant verses of the Qur’an. These verses are analyzed and classified into three main categories: (1) the conceptual definition and moral-spiritual obligation of birr al-wālidayn, (2) the concrete form of expression of gratitude and recognition for the sacrifice of one’s parents, and (3) a firm warning against disobedient behavior that can have adverse consequences, both in this world and in the hereafter. The findings of this study show that birr al-wālidayn not only demands respect and obedience, but also includes gentleness of speech, sincere prayer, providing for, and consistent affection. In conclusion, birr al-wālidayn is not only a social norm but a real manifestation of monotheism and worship, which needs to continue to be contextualized in modern life through an innovative and constructive approach to interpretation.